COMPETITIVE STRATEGIES ANALYSIS AT MSME'S ID CAKE AND BAKERY BUKITTINGGI - Lestari, Sindi Ayu (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2024)
Micro, Small and Medium Enterprises (MSME’S) activities are a business sector that is classified as independent and can develop and be consistent in the national economy. With strategies created by each company or MSME’S, companies can compete more effectively to become superior in their market scope. This research aims to determine the competitive strategy set by  MSME’s ID Cake and Bakery in Bukittinggi City in running their business to be able to face competition. This research uses a qualitative approach with a case study method. Data collection was carried out through interviews and documentation. The research results show that the attraction of buyers to MSME’s ID Cake and Bakery is that the prices offered are relatively cheap or affordable with standard to good quality, MSME’s ID Cake and Bakery gets raw materials from local suppliers using a pre-order system. New competition has quite an influence on MSME’s ID Cake and Bakery, thus MSME’s ID Cake and Bakery carries out market analysis. MSME’s ID Cake and Bakery promotional media is through social media Instagram and Facebook. The economic factor that affects the company is inflation which causes the price of goods to rise, hence MSME’s ID Cake and Bakery has to increase the price of goods. MSME’s ID Cake and Bakery carry out marketing str ategies by utilizing technology such as social media.